Cell differentiation: What have we learned in 50 years?. (21st January 2020) - Newman, Stuart A.
Highlights: Cell differentiation has been modeled as dynamical or modular. Current models draw on both approaches but neglect metazoan-specific gene regulation. Condensed-phase nuclear hubs can exaggerate ancestral gene activities. Enhancers and other regulatory novelties generate cell types from inherent functions. Recruitment of Grainyhead for epithelium exemplifies evolution of differentiation. Abstract: I revisit two theories of cell differentiation in multicellular organisms published a half-century ago, Stuart Kauffman's global genome regulatory dynamics (GGRD) model and Roy Britten's and Eric Davidson's modular gene regulatory network (MGRN) model, in light of newer knowledge of mechanisms of gene regulation in the metazoans (animals). The two models continue to inform hypotheses and computational studies of differentiation of lineage-adjacent cell types. However, their shared notion (based on bacterial regulatory systems) of gene switches and networks built from them have constrained progress in understanding the dynamics and evolution of differentiation. Recent work has described unique write-read-rewrite chromatin-based expression encoding in eukaryotes, as well metazoan-specific processes of gene activation and silencing in condensed-phase, enhancer-recruiting regulatory hubs, employing disordered proteins, including transcription factors, with context-dependent identities. These findings suggest an evolutionary scenario in which the origination of differentiation in animals, rather than depending exclusively on adaptive natural selection, emerged as a consequence of a type of multicellularity in which the novel metazoan gene regulatory apparatus was readily mobilized to amplify and exaggerate inherent cell functions of unicellular ancestors. The plausibility of this hypothesis is illustrated by the evolution of the developmental role of Grainyhead-like in the formation of epithelium.